Life cycles in polar arthropods - flexible or programmed? - Danks, Hugh V.
Climate features that influence life cycles, notably severity, seasonality, unpredictability and variability, are summarized for different polar zones. The zones differ widely in these factors and how they are combined. For example, seasonality is markedly reduced by oceanic influences in the Subantarctic. Information about the life cycles of Arctic and Antarctic arthropods is reviewed to assess the relative contributions of flexibility and programming to life cycles in polar regions. A wide range of life cycles occurs in polar arthropods and, when whole life cycles are considered, fixed or programmed elements are well represented, in contrast to some recent opinions that emphasize the prevalence of flexible or opportunistic responses. Programmed responses ale especially common for controlling the appearance of stages that are sensitive to adverse conditions, such as the reproductive adult. The relative contribution of flexibility and programming to different life cycles is correlated with taxonomic affinity (which establishes the general lifecycle framework for a species), and with climatic zone, the habitats of immature and adult stages, and food. Hugh V. Danks Lit